Gotong Royong Membantu Nelayan Membersihkan dan pengeringan Rumput Laut di Pantai Amal Kec. Tarakan Timur - Nurul Hidayat; Mengsi Mengsi; Maria Rosita; Sulaiman Sulaiman; Lola Tersya Fitriani; Juni Satu; Yustinus Jemi (Karunia: Jurnal Hasil Pengabdian Masyarakat Indonesia, 2025)
This Community Service activity aims to foster a spirit of mutual cooperation and to assist local fishermen engaged in seaweed businesses in the processing and cleaning of their harvests in the Amal Beach Area, East Tarakan District. Seaweed harvested from the sea needs to undergo a thorough cleaning process to maintain its quality, ensure market readiness, and meet industry standards. The activity was carried out by six implementers who collaborated directly with the local fishermen through mutual cooperation, seaweed cleaning, and education on environmentally friendly sea product management. The implementation methods included field observation, guidance, and hands-on practice at the fishermen’s business locations to provide practical understanding. The results indicated improved efficiency in the seaweed processing chain, from cleaning to storage, thereby reducing the risk of damage and quality loss. Additionally, the fishermen’s awareness of the importance of maintaining cleanliness and the balance of coastal ecosystems increased significantly. This activity also strengthened social bonds between students and the fishing community, fostering harmonious communication, and instilling values of togetherness, environmental care, and social responsibility. The positive impact of this program is expected to serve as a sustainable model for sea product management while promoting a collaborative culture between academics and coastal communities.